Performance of 5G mmWave Massive MIMO System with Hybrid Beamforming - Muhammad Zulfiqri Razali; Norshidah binti Katiran; Nurulhuda Ismail (Journal of Electronic Voltage and Application, 2026)
Massive MIMO integrated with beamforming constitutes a fundamental physical layer mechanism in 5G, leveraging large-scale antenna arrays to realize spatial multiplexing gains and array gain for enhanced spectral efficiency (SE), particularly in high-frequency (mmWave) bands suffering from severe path loss. Hybrid beamforming (HBF) has the potential to reduce cost and power consumption compared to fully digital beamforming (DBF). This paper investigates the effectiveness of hybrid beamforming integrated with Joint Spatial Division Multiplexing using Joint Group Processing (JSDM-JGP) in reducing the number of required radio frequency (RF) chains. A comparative analysis between JSDM-JGP and DBF is conducted to examine the trade-offs between reduced system complexity and potential performance enhancements. Our numerical results demonstrate that HBF with JSDM-JGP can significantly improve system energy efficiency (EE) performance with a lower complexity than DBF system. On the other hand, the spectral efficiency (SE) of HBF is slightly lower compared to DBF. In terms of bit error rate (BER), both HDF and DBF show extremely similar results.